Numerical investigation of wave elevation and bottom pressure generated by a planing hull in finite-depth water. (June 2016) - Tafuni, Angelantonio; Sahin, Iskender; Hyman, Mark
Abstract : Highlights: Waves and bottom pressure generated by a planing hull in finite-depth water are investigated. The numerical methodology employed is Smoothed Particle Hydrodynamics. A validation study on transom-stern flow is presented. During planing, high pressure develops below amidships, behind which a V-shaped low-pressure wedge is observed. The low-pressure wedge angle follows the behavior of the surface wake angle. Abstract: A numerical investigation of the bottom pressure and wave elevation generated by a planing hull in finite-depth water is presented. While the existing literature addresses the free-surface deformation and pressure field at the seafloor independently, this work proposes a direct comparison between the two hydrodynamic quantities. The dependence of the pressure disturbances at the ocean floor from the waves generated at the free-surface by a planing hull is studied for several values of both the depth and hull Froude numbers. The methodology employed is Smoothed Particle Hydrodynamics (SPH), a numerical technique based on the discretization of the continuum fields of hydrodynamics through mesh-less particles. The SPH code herein chosen is initially validated against experimental data for transom-stern flow. Subsequently, numerical simulations are presented for a planing hull in high-speed regimes. The results show a direct correlation between surface wave dynamics and hydrodynamic pressure disturbances at the seafloor as the value of the Froude number is varied. This is assessed by studying the inverse dependence of the low-pressure wake angle with the Froude number and by comparison of SPH results with similar works in the cited literature.